The relevance of hierarchical learning theory of Gagne in Nepal - Karna, Manoj Kumar (Patan Prospective Journal, 2023)
After the eldest and the only central Tribhuvan University (TU) in Nepal, there are rest sixteen universities out of which some are regional and some other are related to particular stream of higher study. Reportedly in media and from different sources, TU alone is the faith of around eighty percent student of Nepalese students. Despite having science & technical, humanity & social sciences, management, law, agriculture and so on like opportunities of the studies in the Nepalese universities, now-a-days, a trend is in Nepal in the higher education level that the students prefer to go abroad. This is a big question mark on the learning pattern and the content of teaching for the stake holders and the government of Nepal. This research article tries to discuss on the relevant possible learning theory and some current different perspectives of higher education in Nepal from textbook and media sources giving focus on TU, thus, following the qualitative method. This study will help us an opportunity to discuss different learning theories among academic people in Nepal for qualitative teaching to cater the problems of Nepalese learners.